Project Soothe: A pilot study evaluating the mood effects of soothing images collected using a citizen science approach - MacLennan, Keren; Schwannauer, Matthias; McLaughlin, Angela L.; Allan, Stephanie; Blackwell, Simon E.; Ashworth, Fiona; Chan, Stella W. Y. (Wellcome open research, 2023)
Background Mentally-generated soothing imagery is a therapeutic technique to support mental wellbeing, but some individuals may require support using externally presented stimuli. Project Soothe was launched to collect soothing images using a citizen science approach. This online pilot study evaluated the first 575 soothing images collected, examining: 1) if the images were perceived to be soothing; 2) if viewing the images had a positive impact on mood; and 3) if mood effects were influenced by individual differences in age, gender and depressive symptoms. Methods We recruited 1152 participants (13 – 79 years, M = 35.62, SD = 14.60; 77% female). Participants were randomly allocated to one of 23 sets, each containing 25 images (n = 50 per set) and asked to rate their emotional response (soothed, excited, and anxious) to each image. Participants also reported their mood states pre- and post-viewing the images (using the International Positive and Negative Affect Schedule – Short Form). Results Project Soothe images were rated to be significantly more soothing than anxiety- or excitement-inducing. Further, viewing 25 images was significantly associated with an increase in positive affect and decrease in negative affect. These effects were associated with age and depressive symptoms, with older individuals and those with lower depressive symptoms being associated with more positive changes in mood. Conclusions This pilot study provides preliminary evidence that these soothing images can promote positive mood changes. Further work can now replicate these findings in larger-scale studies with comparison groups and extended outcome variables. The images and associated data have been made available in a data repository (OSF) as a free resource for researchers and practitioners. It is hoped that these images can be developed into useful therapeutic resources.